Optimal Raw Material Mix for the Production of Rice Husk Ash Blended Cement - Raheem, Akeem Ayinde; Kareem, Mutiu Abiodun (International Journal of Sustainable Construction Engineering and Technology, 2017)
Rice husk is the residue left after the grain is removed. Previous studies considered the conversion of rice husk into useful material by incorporating its ash into cement on site. However, the mixing on site was arbitrary. In this study, the optimization of Rice Husk Ash (RHA) blended cement in a cement factory was carried out. Fourteen (14) experimental runs of RHA-blended cements were generated using three-factor D-optimal design (RHA, Ordinary Portland Cement (OPC) clinker and gypsum). The chemical compositions of RHA, OPC-clinker and RHA-blended cements produced were determined using X-ray fluorescence analyzer. The physical properties of the RHA-blended cement produced were also determined. Design-Expert 6.0.8 was used to optimize the RHA-blended cement. The optimum mixture components for the production of RHA-blended cement were 12.45% RHA, 83.44 % OPC-clinker and 4.11 % gypsum. The Â D-optimal design was effective in enhancing the properties of RHA blended cement.